Screening of ligninolytic enzymes produced by Ganoderma lucidum in solid residues from the Amazon (Research, Society and Development, 2022)
White rot fungi have one of the most efficient oxidative lignin degradation systems, and present an enzymatic complex that is responsible for digesting lignocellulosic matter. The aim of this study was to evaluate the production of laccase and total peroxidases by Ganoderma lucidum via solid-state fermentation using açaí seeds and marupá (Simarouba amara) sawdust unsupplemented and supplemented with wheat, corn and rice bran. G. lucidum was inoculated in substrates prepared with the residues and incubated at 25 ºC. Enzymatic extractions were performed on the culture substrates every 2 days for 30 days. The enzymatic activities were determined using ABTS (2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt), with the addition of the enzymatic cofactor H2O2 for total peroxidases. The laccase activity was higher in the supplemented residues, with emphasis on the açaí-based substrate on the 16th day of cultivation, while in marupá the maximum activity was on the 6th day. In the unsupplemented açaí residue, the maximum peak of activity was on the 8th day and, in marupá, no fungal growth was observed. As for total peroxidases, G. lucidum cultivated in the supplemented açaí substrates showed activity peaks on the 8th, 12th, 16th and 28th day, and on 6th and 12th day under unsupplemented conditions. While, in the marupá, total peroxidase activity was observed only on the 6th day of cultivation. Thus, G. lucidum showed potential for producing laccases and total peroxidases, with the substrate supplementation inducing the synthesis of these enzymes.